Increasing Effectiveness Through Process Engineering at Community Development (COMDEV) Lentera Huma Berhati - Irfan Mayendra Putra; Franciskus Antonius Alijoyo (Jurnal Info Sains : Informatika dan Sains, 2023)
This research analyzes efforts to optimize educational programs at the non- profit organization Lentera Huma Berhati Community Development through the application of process engineering. In the context of education for disadvantaged communities, a comprehensive evaluation was conducted to understand the impact of process engineering implementation on program effectiveness. Findings show significant improvements in operational efficiency, optimization of learning time, and improvement in teaching quality. Parent participation has also increased, creating a more inclusive learning environment. The application of process engineering not only changes operations, but also forms the basis for the development of sustainable education programs in the future. With continuous monitoring, Lentera Huma Berhati can continue to adapt to changes in the educational environment and have a positive impact on the communities it serves. This study provides insight into the potential and challenges of process engineering in improving the effectiveness of educational programs in nonprofit organizations focused on community development.